High test-retest reliability of a neural index of rapid automatic discrimination of unfamiliar individual faces. Issue 2 (7th February 2019) - Dzhelyova, Milena; Jacques, Corentin; Dormal, Giulia; Michel, Caroline; Schiltz, Christine; Rossion, Bruno
ABSTRACT: An important aspect of human individual face recognition is the ability to discriminate unfamiliar individual. Since many general processes contribute to explicit behavioural performance in individual face discrimination tasks, isolating a measure of unfamiliar individual face discrimination ability in humans is challenging. In recent years, a fast periodic visual stimulation approach (FPVS) has provided objective (frequency-locked) implicit electrophysiological indices of individual face discrimination that are highly sensitive at the individual level within a few minutes of testing. Here we evaluate the test-retest reliability of this response across scalp electroencephalographic (EEG) recording sessions separated by more than two months, in the same 30 individuals. We found no test-retest difference overall across sessions in terms of amplitude and spatial distribution of the EEG individual face discrimination response. Moreover, with only 4 stimulation sequences corresponding to 4 min of recordings per session, the individual face discrimination response was highly reliable in terms of amplitude, spatial distribution, and shape. Together with previous observations, these results strengthen the diagnostic value of FPVS-EEG as an objective and rapid flag for specific difficulties at individual face recognition in the human population.